Enzyme regulation and coenzymes - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Metal ions, Coenzymes, Control of enzyme concentration (synthesis, degradation), Control of enzyme activity (covalent and/or allosteric modification), Aspartate carbamoyl transferase allostery, Chymotrypsin activation
Reviewed at 2022/11/27